Evaluation Report on Accessibility and Impact of Beneficiary Oriented Programmes on Rural Women - Planning Commission (Planning Commission, 1987)
There is a general feeling that the benefits of the development programmes have not reached the rural women and they have not got their due share. It was, therefore, decided by the Planning Commission to ascertain the actual position by undertaking a case study on Accessibility and Impact of Beneficiary Oriented Programmes on Rural Women. 2. For this purpose, three main rural poverty alleviation programmes, namely integrated Rural Development Programme (RDM), National Rural Employment Programme (NREP) and Allotment of House Site/Construction Assistance/Constructed Houses were selected for process and impact evaluation. The study mainly aimed at to find out the (i) extent and nature of availability of these programmes to the target group, (ii) accessibility of the programme to Rural Women and (iii) special arrangements, if any, made at village, block and district levels to implement the specific guidelines issued by the Government of India from time to time for involvement of rural women as beneficiaries in these programmes and (iv) socioeconomic impact of these programmes on them.
Programme Evaluation Organisation Planning Commission Government of India New Delhi